Hydrosmart: Sistem Otomatisasi Penyiraman Tanaman Hidroponik - Wibawa, Unggul Adi; Indah, Diyaah Putri; Nurmayanti, Septia; Putri, Saskia Maharani; Zahira, Zalfa Shafa’; Putra, Zebadia Akbar; Zen, Andril Muhammad; Zalzabilla, Alifvia Kityn; Nuki, Fauzan Rizky; Fauzi, M. As’ad; Wisnujati, Andika (Universitas Muhammadiyah Yogyakarta, 2025)
Donorojo Village, Donorojo District, Pacitan has great potential in hydroponic cultivation as an alternative to sustainable agriculture. However, the main challenges faced by farmers are the efficiency of watering and optimal monitoring of plant nutrients. To overcome this problem, this community service activity presents Hydrosmart, a hydroponic plant watering automation system based on Internet of Things (IoT) technology. This system is designed to optimize the use of water and nutrients with humidity sensors and automatic control based on microcontrollers. The purpose of this program was to enhance the knowledge and skills of using technology for sustainable agriculture. The methods used in this program include training and mentoring for hydroponic farmers in designing, operating, and maintaining the Hydrosmart system. In addition, an implementation trial was conducted on a pilot area to measure the effectiveness of the system in increasing watering efficiency and plant productivity. This activity was an innovative solution for hydroponic farmers in Donorojo in increasing agricultural yields more efficiently and sustainably. In addition, the implementation of this technology also had the potential to improve farmer welfare through resource efficiency and increased production. By implemented Hydrosmart, the people of Donorojo Village are expected to be more prepared to face the challenges of modern technology-based agriculture